The Berkeley Dry Eye Flow Chart: A fast, functional screening instrument for contact lens-induced dryness - Graham, Andrew D.; Lundgrin, Erika L.; Lin, Meng C. (PloS one, 2018)
In this article, we introduce a novel flow chart-based screening tool for the categorization of contact lens-induced dryness (CLIDE) and its impact on daily visual activities: the Berkeley Dry Eye Flow Chart (DEFC). One hundred thirty (130) experienced soft contact lens wearers discontinued lens wear for 24 hrs, passed a baseline screening and eye health examination, completed the Ocular Surface Disease Index (OSDI) then were dispensed fresh pairs of their habitual lenses. After 6 hrs of wear, subjects were administered a battery of symptom questionnaires, and underwent non-invasive tear breakup time (NITBUT) measurement, grading of distortion in reflected topographer mires, grading of lens surface wettability, and a fluorescein examination of the ocular surface. Subjects returned after at least 48 hrs and repeated all assessments after 6 hrs of wear of a second fresh pair of habitual lenses. The repeatability of the DEFC between visits was within 1%, and Limits of Agreement and Coefficient of Repeatability were comparable to those of the other CLIDE assessments. Higher DEFC score was significantly related to shorter pre-lens NITBUT, higher OSDI score, and higher Visual Analog Scale (VAS) ratings of average and end-of-day severity and frequency of dryness (all p < 0.001). For CLIDE as diagnosed based on DEFC score, the highest sensitivities and specificities were achieved by the OSDI and VAS ratings; pre-lens NITBUT exhibited good sensitivity but poor specificity. The optimum pre-lens NITBUT diagnostic threshold was found to be ≤ 2.0 sec for debilitating CLIDE, and the OSDI threshold was ≥ 11.4. The DEFC provides a means of quickly categorizing CLIDE patients based on severity and frequency of symptoms, and on the degree to which symptoms impact daily life. The DEFC has several potential advantages as a CLIDE screening and monitoring tool, has good repeatability, and is significantly related to commonly employed clinical assessments for CLIDE.